2003
DOI: 10.1109/jstqe.2002.807976
|View full text |Cite
|
Sign up to set email alerts
|

Superluminal pulse propagation in linear and nonlinear photonic grating structures

Abstract: Optical pulse propagation in photonic grating structures can show anomalous (i.e., superluminal or negative) group velocities under certain circumstances owing to the anomalous dispersive properties induced by the periodic grating structure. Such phenomena can be observed for either linear pulse propagation in passive dielectric grating structures, such as in fiber Bragg gratings (FBGs), as well as in frequency-conversion processes exploiting second-order cascading effects in quasi-phase-matched (QPM) nonlinea… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

4
24
0

Year Published

2004
2004
2024
2024

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 39 publications
(28 citation statements)
references
References 54 publications
(117 reference statements)
4
24
0
Order By: Relevance
“…[23,6] In the time domain, the main (highest) peak of the output pulse does indeed appear before the peak of the input pulse. Figure 9 shows the output pulses at the through and drop ports as well as in the input pulse.…”
Section: Finite Casementioning
confidence: 95%
“…[23,6] In the time domain, the main (highest) peak of the output pulse does indeed appear before the peak of the input pulse. Figure 9 shows the output pulses at the through and drop ports as well as in the input pulse.…”
Section: Finite Casementioning
confidence: 95%
“…9 This has recently been demonstrated experimentally for linear and nonlinear gratings. [10][11][12] We here show numerically that pulse delays and advancements can be obtained in optical fibers using acoustooptic coupling between two co-propagating optical modes. 13 A single acoustooptic interaction region, and a configuration based on two acoustooptic interaction regions, separated by a section of unperturbed fiber, are simulated.…”
Section: Introductionmentioning
confidence: 85%
“…In these investigations, the main focus was on the transmission of a pulse through the medium. In experiments, Longhi et al [12,13] first observed superluminal reflection of an optical pulse by using a double-Lorentzian fiber Bragg grating. Later, Nimtz et al [14] experimentally verified that the reflection delay was almost independent of the barrier's length (this effect is known as the Hartman effect [15]).…”
Section: Introductionmentioning
confidence: 99%